An Evaluation of the Ghanaian Kindergarten’s Standard-Based Curriculum - Adam, Abu; Abdallah, Soma (Journal of Education and Practice, 2026)
Purpose: This manuscript is an evaluation of the Ghanaian KG standard-based curriculum. It ascertains its ability to promote an integrated thematic approach to teaching and learning using Scriven’s Goal-free model of evaluation. Methodology: A rapid approach to systematic review was used to gather relevant information and critically appraise the programme. Out of a total 31, 15 manuscripts were selected for an in-depth analysis. Ninety-six (96) teachers’ lessons were observed. Findings: The evaluation reveals that thematic integrated curriculum is endorsed by many scholars as an efficient approach to teaching and learning in kindergarten education. The Ghanaian standard-based curriculum promotes intradisciplinary thematic integration demonstrated in Our-World-Our-People as a combination of multiple subject areas into one. Interdisciplinary thematic integration was not practiced by most teachers because the KG curriculum does not explicitly say how it is achieved in individual subjects. Unique Contribution to Theory, Practice and Policy: The study recommended that teachers should see the themes outlined under other subjects as subject-specific knowledge and skills that their lessons should s and develop sub-themes from the seven (7) broad themes for the other subjects.